PENERAPAN MODEL MISSOURI MATHEMATICS PROJECT (MMP) UNTUK MENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IV SEKOLAH DASAR - Rohman, Taufik (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
This research is motivated by the low ability of students' mathematical problem solving in learning mathematics. To improve students' mathematical problem-solving skills, researchers implemented the Missouri Mathematics Project (MMP) carried out in five steps, namely Review (Apperception), Development (Development), Cooperative working (group work), Seatwork (independent work), Assignment (Assignment). The purpose of this research is to (1) explain the implementation of learning by applying the Missouri Mathematics Project (MMP) model. (2) explaining the increase in mathematical problem solving abilities by applying the Missouri Mathematics Project model. The model used is quantitative using quasi-experimental methods and samples consisting of two classes as an experimental class and a control class with test research instruments (pretest and post-test) and observation of the learning process. This research was conducted at SDN Rawa, Sukahening District, Tasikmalaya Regency. Based on the results of observations, it shows that the process of learning mathematics by applying the Missouri Mathematics Project (MMP) model has changed. This can be seen from the significantly different student learning outcomes after being analyzed using SPSS 29 with the Mann-Whitney U-Test, the test results show Sig = 0.000 < = 0.05 then Ho is rejected. So it can be concluded that there are differences in student learning outcomes between the experimental class and the control class using the Missouri Mathematics Project (MMP) learning model is better than conventional learning.